Phone call for diabetic people: protocol for a pragmatic, type 1 effectiveness-implementation hybrid clinical trial - Danila Cristina Paquier Sala; Paula Cristina Pereira Costa; Ana A. Baumann; Marília Mastrocolla de Almeida Cardoso; Ana Lucia de Moraes Horta; Meiry Fernanda Pinto Okuno (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To describe an implementation study protocol for an intervention based on educational guidelines focused on seven self-care behaviors, through phone calls to individuals with type 2 diabetes. Method: We will conduct a hybrid type 1 effectiveness-implementation pragmatic randomized clinical trial, with 198 individuals with type 2 diabetes on insulin therapy, from the Glycemic Self-Monitoring Program of two Primary Health Care in the city of São Paulo and three in Campinas, located in the state of Sao Paulo. Patients will be allocated in a 1:1 ratio to either the intervention or control group. Both groups will receive standard care, with the intervention group also receiving a phone call. During the call, nurses will provide guidance based on seven self-care behaviors, known as The ADCES7 Self-Care Behaviors™. Evaluations will happen at the baseline, and after 3- and 6-months post initiation of the trial. Glycemic levels and adherence to self-care behaviors will be compared before and after the intervention using multiple linear regression models. Through interviews with participants from the intervention group, implementation determinants based on the Capability, Opportunity, Motivation-Behavior (COM-B) model, and implementation outcomes feasibility, acceptability, and appropriateness will be evaluated. Expected outcomes: We will evaluate the effectiveness of an intervention while exploring contextual conditions for its implementation in clinical practice of Primary Health Care. This study will provide preliminary evidence on the effectiveness of educational guidance through nurse-led telephone calls, as well as implementation determinants and outcomes in the clinical practice of Primary Health Care. Its results are important for expanding this assistance in locations where nursing consultation for people with diabetes is absent, hindered, or restricted. Study is registered on the ReBEC platform.